Geographical distribution and conservation of a rare medicinal plant Munronia pinnata (Wall.) Theob. (Meliaceae) in Sri Lanka - Dharmadasa, R. M.; Hettiarachchi, P. L.; Premakumara, G. A.S. (Bangladesh Journal of Plant Taxonomy, 2011)
In the present study, distribution and abundance of Munronia pinnata (Wall.) Theob. in Sri Lanka were explored in 6 provinces, 7 districts, 68 Divisional Secretariat Divisions (DSD) and 395 Grama Niladari (GN) areas. Fifty three GN areas were identified as M. pinnata abundant areas. In 217 GN areas, the plant is found in small scale and in 65 GN areas it was rarely found. M. pinnata was not found in 8 DSDs. Ten new localities were found and three of them were in the wet zone. The highest diversity was found in Monaragala and Matale districts. Populations well adopted for a range of climatic conditions were observed in Madulla, Nilgala, Warakapola, Ritigala and Haldumulla. Monaragala, Wellawaya, Mathurata, Meemure and Kithulpe were identified as unique populations for conservation. Monaragala, Badulla and Matale appear to be the most suitable districts for commercial cultivation of M. pinnata. This is the first record of an extensive systematic survey on the distribution of M. pinnata in Sri Lanka. Key words: Munronia pinnata; Systematic survey; Meliaceae; Conservation; Cultivation; Medicinal plants. DOI: 10.3329/bjpt.v18i1.7837 Bangladesh J. Plant Taxon. 18(1): 39-49, 2011 (June)